MAGIC3D FDTD EM-PIC code cut cell slow wave serpentine calculation - Woods, Andrew; Ludeking, L. (2015)
© 2015 IEEE. The MAGIC3D finite difference electromagnetic particle-in-cell (FDTD EM-PIC) code has been upgraded to include non-conformal or 'cut' cells. The code solves Maxwell's equations in Cartesian coordinates using full and partial cells cut arbitrarily along flat surfaces. The sophisticated cut cell treatment enables cells to be sliced in all directions and fractions. A field remapping algorithm combines small volumes into neighbor cells to prevent undue Courant time step limitations. The code has been applied to reduced generic serpentine slow wave structures with incoming EM and particle beams in order to explore benefits of cut cells in deliberately marginally-zoned treatments. Improved power transmission was seen with cut cells. Reduced unwanted noise occurred in the particle beam case. Benefits were tracked to the smoother geometry of the serpentine sections with cut cells.